2022
DOI: 10.1002/adfm.202207821
|View full text |Cite
|
Sign up to set email alerts
|

Silane‐Mediated Expansion of Domains in Si‐Doped κ‐Ga2O3 Epitaxy and its Impact on the In‐Plane Electronic Conduction

Abstract: Unintentionally doped (001)-oriented orthorhombic κ-Ga 2 O 3 epitaxial films on c-plane sapphire substrates are characterized by the presence of ≈ 10 nm wide columnar rotational domains that can severely inhibit in-plane electronic conduction. Comparing the in-and out-of-plane resistance on well-defined sample geometries, it is experimentally proved that the in-plane resistivity is at least ten times higher than the out-of-plane one. The introduction of silane during metal-organic vapor phase epitaxial growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 69 publications
0
20
0
Order By: Relevance
“…It is worth noting here that often the literature indifferently reports κ-and ε-Ga 2 O 3 ; this ambiguity originates from the six-fold symmetry of early diffraction patterns and the consequent classification of such Ga 2 O 3 phase as "hexagonal", hence the ε-Ga 2 O 3 ascription. A comprehensive TEM study 20 , as well as other works recently published [21][22][23][24] , showed definitely that the so-called κ phase is indeed orthorhombic and not hexagonal. In analogy to the usual nomenclature of other metal-oxides, it is therefore correct to denominate the orthorhombic phase as κ, as it will be done in this paper.…”
Section: Introductionmentioning
confidence: 87%
“…It is worth noting here that often the literature indifferently reports κ-and ε-Ga 2 O 3 ; this ambiguity originates from the six-fold symmetry of early diffraction patterns and the consequent classification of such Ga 2 O 3 phase as "hexagonal", hence the ε-Ga 2 O 3 ascription. A comprehensive TEM study 20 , as well as other works recently published [21][22][23][24] , showed definitely that the so-called κ phase is indeed orthorhombic and not hexagonal. In analogy to the usual nomenclature of other metal-oxides, it is therefore correct to denominate the orthorhombic phase as κ, as it will be done in this paper.…”
Section: Introductionmentioning
confidence: 87%
“…Among the possible phenomena leading to the observed alteration of the doping profile, the thermally activated out-diffusion of hydrogen is certainly a plausible hypothesis; in fact, interstitial hydrogen is expected to be a shallow donor in κ-Ga 2 O 3 , as already predicted for β-Ga 2 O 3 . Hydrogen can derive from the precursors and the carrier gas in κ-Ga 2 O 3 layers. , In κ-Ga 2 O 3 layers grown using H 2 carrier gas but without providing an additional silane (SiH 4 ) flow, resistivity of about 10 5 Ω·cm was typically obtained. , This implies that only a minor fraction of molecular hydrogen gas acts as a shallow donor, but we cannot exclude that a much more effective hydrogen incorporation may take place when the silane gas cracks at the surface of the growing κ-Ga 2 O 3 layers, with release of atomic H. Therefore, it is plausible that both atomic hydrogen and silicon can contribute to establish the n-type conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that we also analyzed the effect of different mobility values in-plane and perpendicular to the junction. Such anisotropy in the mobility values originates from the formation of columnar domains in the κ-Ga 2 O 3 . It can be noted that the dominant transport mechanism for in-plane conduction is the variable range hopping, leading to low mobility values .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The defects are mostly perfectly vertically oriented, i.e., 3 × 120°rotated domains and antiphase boundaries. 7,23,24 In addition, these vertically oriented structural defects could be electrically charged. 24 On the other hand, the first-principles calculations of Zeman et al do not contain the charged structural defects, vertically oriented and rotated domains, and antiphase boundaries.…”
mentioning
confidence: 99%